HUBUNGAN PELAKSANAAN CUCI TANGAN OLEH PERAWAT SEBELUM DAN SESUDAH BERINTERAKSI DENGAN PASIEN TENTANG PENCEGAHAN INFEKSI NOSOKOMIAL DI RS PTPN II BANGKATAN BINJAI TAHUN 2017 - Yunita Sarah Nadeak (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Washing your hands is a simple thing to remove dirt or germs and minimize germs that are in your hands, by pouring water over. and can be done by adding certain ingredients such as soap. With this connection the implementation of hand washing by nurses before and after interacting with patients about prevention of infection, this type of research is a survey research method used to collect data or information about the success of the implementation of hand washing. The population in this study was nurses. The sample used was disobedience to nurses in hand washing before and after interacting with patients. The sampling technique is total sampling. Data analysis with chi-square test technique using the SPSS (Statiscal Product and Service Solution) program. From the results of the study the relationship between the implementation of hand washing by nurses before and after interacting with patients about prevention of nosocomial infections So Ha was accepted and Ho was rejected. There is a significant relationship between Knowledge and hand washing by nurses before and after interacting with patients about prevention of nosocomial infections at Rs. Ptpn 2 for the city of Binjai, so that respondents are expected to seek more knowledge about steps and compliance with hand washing.Keywords: Relationship of Hand Washing by Nurses, Prevent Infection